The Relationship Between The Concept of Pdr and The Practice of Brown & Levinson’s Politeness Strategies by Indonesian Caregivers in The Domain of Elderly Care in Japan - Putu Dewi Merlyna Yuda Pramesti; N.L., Sutjiati Beratha; Made Budiarsa; I Nengah Sudipa (e-Journal of Linguistics, 2019)
An important topic of pragmatic studies is politeness. To be able to deliver messagessuccessfully in a speech act, politeness is believed to be an important means that can be used toreduce inconvenience in communication process. This article is a piece of research to support adissertion that examines politeness in communicating in Japanese by Indonesian caregiverstowards the elderly in Japan. Specifically, this article examines the relationship between PDR(power, distance, rank of imposition) concept and the practice of Brown&Levinson‟s politenessstrategies by the Indonesian caregivers towards the elderly in Japan. This study appliesqualitative method. The type of data used is primary data in the forms of utterances from theIndonesian caregivers towards the elderly. The Indonesian caregivers who are the subjects of thestudy work at 6 elderly care homes in Japan. These six homes were chosen as research locationsas they hire more Indonesian caregivers compared to other homes. The results of the analysisindicate that there is relationship between the concept of PDR and the practice ofBrown&Levinson‟s politeness strategies in the utterances of the caregivers towards the elderly;however, the two concepts of Brown&Levinsoncan cannot be fully applied in the utterances ofthe Indonesian caregivers in the context of taking care of the elderly. The Indonesian caregiversapplied positive and negative politeness strategies in their utterances towards the elderly, as thechoice of the politeness is highly dependent on the situational contexts where the utterances takeplace.